2022
DOI: 10.3390/pharmaceutics14112381
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Properties, and Release Kinetics of the Polymer/Insect Repellent System Poly (l-Lactic Acid)/Ethyl Butylacetylaminopropionate (PLLA/IR3535)

Abstract: The insect repellent ethyl butylacetylaminopropionate (IR3535) was used as a functional additive for poly (l-lactic acid) (PLLA) to modify its structure and mechanical properties and achieve insect repellency. PLLA/IR3535 mixtures at various compositions were prepared via melt extrusion. In the analyzed composition range of 0 to 23 m% IR3535, PLLA and IR3535 were miscible at the length scale represented by the glass transition temperature. Addition of IR3535 resulted in a significant decrease in the glass tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Incorporating the repellent IR3535 into bio-sourced and biodegradable PLLA opens the way to the realization of an environment-friendly repellent-delivery device. After successful testing of melt extrusion , and 3D printing of semi-finished and final products of the PLLA/IR3535 system, in this work, electrospinning of fiber mats as an alternative technology for obtaining such an environment-friendly repellent-delivery system is investigated. By systematic variation of the electrospinning parameters, including voltage, nozzle-to-collector distance, flow rate, and solution composition, uniform fibers with a diameter close to 1 μm and containing a large amount of the repellent, exceeding 40 m%, were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Incorporating the repellent IR3535 into bio-sourced and biodegradable PLLA opens the way to the realization of an environment-friendly repellent-delivery device. After successful testing of melt extrusion , and 3D printing of semi-finished and final products of the PLLA/IR3535 system, in this work, electrospinning of fiber mats as an alternative technology for obtaining such an environment-friendly repellent-delivery system is investigated. By systematic variation of the electrospinning parameters, including voltage, nozzle-to-collector distance, flow rate, and solution composition, uniform fibers with a diameter close to 1 μm and containing a large amount of the repellent, exceeding 40 m%, were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…By systematic variation of the electrospinning parameters, including voltage, nozzle-to-collector distance, flow rate, and solution composition, uniform fibers with a diameter close to 1 μm and containing a large amount of the repellent, exceeding 40 m%, were obtained. Such a high amount of repellent was impossible to incorporate into the polymeric carrier by melt extrusion and 3D printing, ,, where only up to about 25 m% IR3535 was added. Thermal and structural analyses revealed that IR3535 results in a decrease in the glass transition temperature of the polymer component, confirming thermodynamic solubility, as suggested in earlier works, , and causing plasticization of the amorphous PLLA phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations